2022
DOI: 10.3390/polym14225018
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bioactive Opuntia ficus-indica Edible Films Containing Probiotics as a Coating for Fresh-Cut Fruit

Abstract: Bioactive edible films have received more attention in recent years as a method for food preservation with value-added functions. The aim of this study was to develop a bioactive edible film containing mucilage of cactus (Opuntia ficus-indica) and incorporating the probiotic strain Enterococcus faecium FM11-2 as an active component to promote consumer health benefits. Opuntia ficus-indica is rich in nutritional and bioactive compounds and the abundance of this cactus makes it attractive for food applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…19 However, in this study, Young's modulus and tensile strength of the probiotic-loaded bilayer (L-SF/SA) were decreased slightly, which may be due to the interruption of polymer cohesion caused by the addition of probiotics. 24 Consistent with our results, Todhanakasem et al 25 found that when probiotics were added, Young's modulus of the membrane prepared from the mixture of gelatin, cactus gum, and sorbitol was significantly decreased. Ebrahimi et al 26 reported that adding probiotic cells to carboxymethyl cellulose (CMC) membranes significantly reduces the tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, in this study, Young's modulus and tensile strength of the probiotic-loaded bilayer (L-SF/SA) were decreased slightly, which may be due to the interruption of polymer cohesion caused by the addition of probiotics. 24 Consistent with our results, Todhanakasem et al 25 found that when probiotics were added, Young's modulus of the membrane prepared from the mixture of gelatin, cactus gum, and sorbitol was significantly decreased. Ebrahimi et al 26 reported that adding probiotic cells to carboxymethyl cellulose (CMC) membranes significantly reduces the tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in weight loss was recorded as the number of storage days increased. In fruits, decrease in weight during storage happens due to the loss of water as a result transpiration (Todhanakasem et al, 2022). The lower weight loss observed in the coated sample could also be due to the characteristics of edible coating formed on the fruit surface which controls the water vapour movement in the fruits.…”
Section: Weight Lossmentioning
confidence: 97%
“…Fruit that has been harvested is prone to rotting, losing nutrients, and becoming brown during storage. Researchers are 55 combined this mucilage and the probiotic strain Enterococcus faecium FM11-2 to create an edible film to preserve freshly cut apple slices. 55 Another study also used cactus fruit mucilage as a coating on loquat fruit.…”
Section: Future Researchmentioning
confidence: 99%
“…Researchers are 55 combined this mucilage and the probiotic strain Enterococcus faecium FM11-2 to create an edible film to preserve freshly cut apple slices. 55 Another study also used cactus fruit mucilage as a coating on loquat fruit. The obtained results showed a significant effect of mucilage coating on the preservation of quality, nutritional value, and sensorial parameters and showed significantly lower microbial growth compared to uncoated loquat fruits during cold storage.…”
Section: Future Researchmentioning
confidence: 99%